STUDI KORELASI ANTARA GAYA KEPEMIMPINAN DAN KEMAMPUAN MANAJERIAL DENGAN KINERJA GURU DI KABUPATEN TULUNGAGUNG - Purwowidodo, Agus (Jurnal Dinamika Penelitian, 2013)
The objective of this research was to abtain the empiric figure ofthe correlation between leadership style and managerial abilitywith the teachers performance in Tulungagung Regency.The population of this research was all elementary shool teachers.Sample of 60 respondents was drawn by the used of simplerandam sampling technique of Taro Yamane formula.Instruments used to gathering data were questionnaires onteachers performance, leadership style and managerial ablity. The data was analyse by the used of simple, multiple and partialcorrelation and regression.The results of this research were, as followed: (1) that there weresignificant relationship between leadership style, and teachersperformance; (2) that there were significant relationship betweenmanagerial ability and teachers performance; (3) that there weresignificant Â relationship between leadership style and managerialability Â as they grouped together and teachers performance.